2008
DOI: 10.1177/1065912907308098
|View full text |Cite
|
Sign up to set email alerts
|

Press Coverage of Mayoral Candidates

Abstract: Some research on gender bias in news coverage of political campaigns indicates that the media portray male and female candidates differently. Research to date, however, has focused only on elections to national or statewide offices, where confounding variables such as party, incumbency, and competitiveness are present. The authors resolve this problem by focusing their analysis of media campaign coverage on nonpartisan, open-seat, and competitive mayoral races. The authors' content analysis of press coverage i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 49 publications
(64 reference statements)
1
7
0
1
Order By: Relevance
“…For instance, in a content analysis of newspaper articles on the 2006 U.S. Senate race, Hayes (2011) finds that female and male politicians do not differ in the amount of reporting devoted to their traits. Similarly, mayoral (Atkeson & Krebs, 2008) and presidential (Meeks, 2013) candidates of both genders are equally likely to receive gender-linked coverage. In general, elections with female candidates tend to yield more news stories on politicians' personal traits than their issue stances (Dunaway et al, 2013), with the media often paying significantly more attention to masculine than feminine traits (e.g., Meeks, 2013).…”
Section: Media Coverage Of Politicians' Traitsmentioning
confidence: 99%
“…For instance, in a content analysis of newspaper articles on the 2006 U.S. Senate race, Hayes (2011) finds that female and male politicians do not differ in the amount of reporting devoted to their traits. Similarly, mayoral (Atkeson & Krebs, 2008) and presidential (Meeks, 2013) candidates of both genders are equally likely to receive gender-linked coverage. In general, elections with female candidates tend to yield more news stories on politicians' personal traits than their issue stances (Dunaway et al, 2013), with the media often paying significantly more attention to masculine than feminine traits (e.g., Meeks, 2013).…”
Section: Media Coverage Of Politicians' Traitsmentioning
confidence: 99%
“…According to Atkeson and Krebb (2008), there are four main approaches to studying gender bias in news reporting of electoral campaigns: studying the volume of media coverage, expressions of candidates' viability, topics/issues, and discussion of the candidates' traits. The volume of coverage usually refers, in radio and television, to the amount of airtime and, in publications, to the number of articles or square centimeters dedicated to candidates.…”
Section: Gender Bias In the Volume Of Media Coverage Of Electoral Cammentioning
confidence: 99%
“…The absence of gender bias in the media coverage of political campaigns is, thus, one of the elements of the much sought after political participation of women in the world. In this regard, some studies carried out in the United States and European countries (Dan & Iorgoveanu, 2013;Hooghe, Jacobs, & Claes, 2015;Kahn, 1994;Ross, Evans, Harrison, Shears, & Wadia, 2013) have found that women candidates are at a disadvantage when competing for media attention, while other studies have found no gender difference in the volume of media coverage (Atkeson & Krebb, 2008;Bystrom, Robertson, & Banwart, 2001;Devitt, 2002;Lachover, 2017;Smith, 1997). Nonetheless, most of the studies report some kind of gender bias, if not in volume, then in qualitative aspects of coverage such as attributions of viability, issue coverage and featured candidate traits.…”
Section: Introductionmentioning
confidence: 99%
“…Para Atkeson & Krebs (2008), lo anterior parece ser más una ventaja que desventaja, debido a que, por ser mujeres, se espera que asuman tópicos femeninos, mientras que, por ser políticas, se espera su involucramiento en temas de orden superior. Wasburn & Wasburn (2011) hallaron que, aunque una candidata tenga consigo una agenda de tópicos importantes para la soberanía nacional, los medios prefieren preguntarle desde ámbitos asistencialistas, hacia los cuáles consideran que deberían poseer una opinión.…”
Section: Encuadre 5: Agenda Temáticaunclassified